How ESG corporate reputation affects sustainability premiums in the insurance industry - Carannante, Maria; D'Amato, Valeria; Staffa, Maria Sole (Frontiers in Applied Mathematics and Statistics, 2024)
Based on increasing ESG awareness, executives, and investment professionals consider ESG factors in strategic and operational decisions. Like other companies, insurers recognize that the ESG transition offers opportunities for long-term value creation. In our research, we evaluate how ESG corporate engagement impacts an insurance company's balance sheet in economic and financial terms, unlocking financial resources throughout the sustainability premium. We resort to the theoretical paradigms of behavioral finance applied to actuarial portfolio evaluations. Our findings show that ESG engagement is significantly performing since it determines higher expected profits. We offer our framework as a tool for the strategic decision-making process.